New BBVA digital bank headquarters in Madrid saves energy using composite sun panels fabricated from Crestapol® infusion resin and Crystic® FIREGUARD intumescent in-mold gelcoat. Issue 2 (March 2016) - Gray, Neil
Abstract : The new digital banking group BBVA headquarters building in Madrid, designed by architecture firm Herzog & de Meuron, is kept cooler using sandwich laminate design composite sun panels which form an integral part of the contemporary new building façade. Summer temperatures in Madrid can reach over 30°C by midday, so having environmentally friendly ways to minimize air-conditioning energy usage inside its new head office was high on the agenda for BBVA, given its strong commitment to using renewable energy and buildings with the highest environmental certification. The use of innovative composite sun panels in front of the glass windows around the new BBVA building achieved this energy saving corporate objective in grand style.